Book Review: The Ethics of Computer Games by Miguel Sicart - Kaplan, Matthew Geyer (Eludamos: Journal for Computer Game Culture, 2010)
This review describes The Ethics of Computer Games, a recent academic release by Miguel Sicart. Sicart uses a philosophical framework of various ethical and ontological theories to analyze how different games and game designs invoke or ignore the moral virtues of the culture in which they exist. According to Sicart, the most ethical games are those which take into account the complex subjective role of the player and the game community, and inscribe in the gameplay a kind of ethical system that either cultivates "virtuous" exploration or challenges the player to come to a specific ethical conclusion based on careful reflection.